Relasi Tasawuf dan Kebudayaan - Fatkhul Wahab (LP3M IAI Al-Qolam Malang, 2020)
Ta?aw?f and culture are two inseparably concepts. Those shall be affiliate to create a synergy in completing for each other. Culture can be defined according to anthropological perspective as the human’s ideas outcomes, customs, social behaviour of a particular people or society, and the other manifestation of human achievement. Culture constitutes of dynamic human creative manifestation, which complies human’s mental (non-material) and physical (material) needs. Material culture tends to has mechanical characteristic, while the non-material one has psychological types. If we relate this definition to ta?aw?f concept, then ta?aw?f indeed involves itself within culture definition. It because ta?aw?f has the very anvil on Al-Qur’an and Hadi?t. Ta?aw?f guides the human beings toward the right path according to their natural tendency which is willing by Allah swt. The technological advance has been mediate human’s culture to the spectacular one. It is not only make people’s life getting easier, but also made people’s life being dependency. We cannot easily getting off from these technological culture which is creating great disaster called comfortableness. The disaster, slowly, consumes people’s leisure time to corrupt their spirituality. In those condition, human being should walking back to ta?aw?f which has balancing aspect to reshaping human’s spirituality. Ta?aw?f means to guide human beings to find their natural tendency again. Ta?aw?f does not mean as killing another nafs aspect within human beings’ souls, but to give it another way to find the true self. Keywords: Culture, spirituality, ta?aw?f.